2013
DOI: 10.1016/j.jcrs.2013.02.053
|View full text |Cite
|
Sign up to set email alerts
|

Phacoemulsification with intraocular lens implantation in patients with anterior uveitis

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 15 publications
1
19
1
1
Order By: Relevance
“…16,17 The incidence of PCO in our study was 18.6% and 21% in the phacoemulsification and SICS groups, respectively (P = 0.678). The incidence of PCO is significantly higher with polymethyl metha acrylate IOLs as compared with acrylic IOLs, and PCO rates do not significantly differ between hydrophobic or hydrophilic acrylic IOLs at 6 months' follow-up.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…16,17 The incidence of PCO in our study was 18.6% and 21% in the phacoemulsification and SICS groups, respectively (P = 0.678). The incidence of PCO is significantly higher with polymethyl metha acrylate IOLs as compared with acrylic IOLs, and PCO rates do not significantly differ between hydrophobic or hydrophilic acrylic IOLs at 6 months' follow-up.…”
Section: Discussionmentioning
confidence: 59%
“…On the first postoperative day, there were more cases of corneal edema (12,17.1%) in the phacoemulsification group than in the SICS group (8,11.4%) (P = 0.046). The mean endothelial cell loss in these patients was 26.8% at 1 week and 31.4% at 6 months in the phacoemulsification group and 22.7% and 26.4% in the SICS group, respectively.…”
Section: Complicationsmentioning
confidence: 95%
“…In another series, Budak et al (1999) reported an incidence of 17.1 % following ECCE or Phacoemulsification with IOL implantation. Kosker et al (2013) reported an incidence of severe post-operative uveitis in 12.7 % of eyes following phacoemulsification in a series of 55 eyes. Tejwani et al (2006) did not find any case of severe post-operative uveitis in a series of 103 eyes.…”
Section: Complicationsmentioning
confidence: 98%
“…The sample size is probably too small to find out any adverse effects such as endophthalmitis, retinal detachment, and vitreous hemorrhage. It deals with an important problem and one that can be frustrating for the cataract surgeon who might feel robbed of success after a perfectly executed cataract (mm Hg) 14.4 ± 4.32 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) 16.4 ± 4.4 14.8 ± 5 13.54 ± 4.2 P = 0.56 P = 0.48 P = 0.6…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Prophylaxis is suggested for in situations where patients who are prone to develop cystoid macular edema following cataract surgery, such as patients with uveitic cataract 7 and those with diabetes. 8,9 In cases that do not resolve spontaneously, a course of topical steroids and non-steroidal anti-inflammatory agents (NSAIDS) helps in the resolution of a large proportion of cases. 10 A certain subset of patients, however, does not respond to topical therapy alone.…”
Section: Introductionmentioning
confidence: 99%